Biodegradation of 2-methylisoborneol by single bacterium in culture media and river water environment. Issue 3 (4th May 2017) - Du, Kang; Zhou, Beihai; Yuan, Rongfang
Abstract: 2-Methylisoborneol (2-MIB) is a typical odorant in water sources. It is difficult for conventional water treatment to remove it. In this study, three strains capable of removing 2-MIB were isolated from activated carbon of sand filter. They were identified to be Shinella zoogloeoides, Bacillus idriensis and Chitinophagaceae bacterium based on 16S rRNA gene sequence analysis. The biodegradation of 2-MIB was improved with the presence of external carbon (glycerol, glucose, etc.). In the period of 20 days, Bacillus idriensis can remove 2 mg L −1 2-MIB to 368.2 and 315.4 μg L −1 in mineral salts medium without and with glycerol. Chitinophagaceae bacterium can remove it to 265.6 and 185.4 μg L −1 without and with glucose. The enzymatic activity of B. Idriensis was lower when external carbon coexisted with 2-MIB. This indicated that a carbon source can inhibit the use of 2-MIB, but it can provide rich nutrients for the growth of bacteria.